الإمام علي بن التركماني وإسهاماته في إثراء التراث النبوي - Walid Mohd Said; Syed Najihuddin Syed Hassan; Amran Abdul Halim; Abdulloh Salaeh; Mohd. Fauzi Mohd. Amin; Nidzamuddin Zakaria; Nor Saadah Musa (Fakulti Pengajian Quran dan Sunnah, 2025)
E-Proceeding The9th International Conference on Nabawi Heritage(SWAN 2024) Theme: Prophetic Legacy in Development of Civil Society in the Era of Artificial Intelligence (AI) 6-7 November 2024